Pengaruh Time Budget Pressure, Komitmen Organisasi,Pemahaman Good Governance dan Kompleksitas Tugas Pada Kinerja Auditor - Susanti, Ni Ketut Ari; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 28 No 2 (2019), 2019)
This study aims to examine the effect of time budget pressure, organizational commitment,  understanding of good governance and complexity of tasks on auditor performance. This  research was conducted at the BPKP Representative of Bali Province. The number of  samples taken was 55 respondents using the saturated sampling method. Data collection  was carried out using a research questionnaire. The data analysis technique used is multiple  linear regression analysis. Based on the results of the analysis, it was found that budget time  pressure and task complexity negatively affected auditor performance. This shows that the  higher the time budget pressure and the complexity of the task causes the auditor's  performance to be lower. While organizational commitment and understanding of good  governance have a positive effect on auditor performance. This shows that the higher  organizational commitment and understanding of good governance lead to higher auditor  performance. Keywords : Performance, time budget, commitment, good governance, complexity.